Ethological and morphological adaptations of Psophus stridulus Linnaeus 1758 to habitat islands (Caelifera: Acrididae). - Bönsel, André (Contributions to Entomology = Beiträge zur Entomologie, 2004)
This article proposes the hypothesis that the Orthopteren species Psophus stridulus restricted itself to habitat islands during its range expansion in the Holocene, and that it is specifically adapted to these. Literature analysis shows, that P. stridulus never colonises large areas, but is always concentrated in small isolated patches. Observations in Poland and Western Siberia corroborate this findings. The hypothesis is supported by the specific autecology and ethology of the species. To verify the hypothesis, a number of ethological, morphological and genetic features of this species can be understood as selective adaptations. In the context of nature conservation, these features have been discussed previously as existence-threatening trends.Recapture experiments in an isolated habitat island in NE Poland showed, that during the imaginal stage males were highly significantly more mobile than the females. On average, the males covered distances of 20 m, the females of 5 m. No pattern could be detected in the males´ movements, their trajectories crossed frequently. Mean size of male home range was 67 m², and of female home range 20 m². Usually the females sat together in clusters. If noticing approaching groups of males by their rattle, the females hid. They were discovered by few or only a single male of the group. After mating, the males left very fast, whereas the females stayed motionless on the same spot. A couple of hours or days later they could be found by another male, and another mating could take place. The discovery of the passive and hidden females might be attributed to short-time excretions of pheromones by the females in low dose. It is possible, that the females are stimulated to excrete pheromones by the rattle of the active males. Compared to females, the males have a significantly higher abundance of Sensilla coeloconica on their antennae, which serve for detection of chemical stimuli. The hidden way of life of the females, who eventually announce their presence by only short-time signals consisting in pheromones, and the high spatial dynamics of the males increase the chance, that more than one male mates with a female, or a male with a number of females, respectively. Besides to the extraordinary unbalanced sex-ratio of P. stridulus, and the females’ ability to store sperm, which were already described in the literature, this paper shows further adaptations for the survival of a species occurring only in habitat islands. For verification of the hypothesis, further investigations to confirm the excretion of pheromones by females, and on the functions of the sensilla are necessary, as well as studies on physiological plasticity of the females, enabling directed investment in an increased proportion of male offspring.KeywordsPsophus stridulus, habitat island, sex-specific movement pattern, sensilla sex dimorphism, adaptation.